Dixie city jam eaudiobook - Burke, James Lee (Dave Robicheaux, 2012)
Somewhere off the coast of Louisiana, an old Nazi submarine lies buried in the sands, hidden by thick seaweed and salty waters. Dave Robicheaux is the only person who has ever discovered it, and now Hippo Bimstine, New Orleans' largest mover and shaker, wants him to find it again.